مناهج التربية الأخلاقية في معهد تحفيظ القرآن للثانوية - Jurais Mahali; Ahmad Alim; Abdul Hayyie Al-kattaniy (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
Islam is a very respectful religion good morals. But in reality there are still many from muslim communities do not uphold morals the morals taught by the prophet shalallahu ‘Alaihi wasalam, there are many moral violations among the younger generation, such as being arrogant, indifferent, promiscuity, atc. This is what encourages the writer to explor the inner moral education curriculum in the book riyadhu As-Sholihin for senior secondary high school education institutions for the upper secondary level of the tahfidz Al-Qur’an. This research is a literature study with a content analysis approach. This research produces a moral education curriculum, some of wich will be described in this article, namely sincere in words and deeds, repent, patient, piety, amar ma’ruf nahi munkar, and tawadu.